2023
DOI: 10.26820/reciamuc/7.(1).enero.2023.187-195
|View full text |Cite
|
Sign up to set email alerts
|

Vitíligo, diagnóstico y tratamiento

Abstract: El vitíligo es una hipomelanosis adquirida manifestada clínicamente por la aparición progresiva de máculas acrómicas e hipocrómicas, a veces con gran repercusión estética y la consiguiente afectación de la autoestima de las personas que la padecen. La metodología utilizada para el presente trabajo de investigación, se enmarca dentro de una revisión bibliográfica de tipo documental, ya que nos vamos a ocupar de temas planteados a nivel teórico como es Vitíligo, diagnóstico y tratamiento. La técnica para la reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…(1) It affects 0,5-1 % of the world's population, regardless of race or gender, and it has been observed that more than 50 % of cases occur before the age of 20. (2) This pathology usually presents as acromic and hypochromic macules, with defined borders and a tendency to symmetry. The topography of the lesions is ubiquitous, with a preference for the acral https://doi.org/10.56294/sctconf2023324 and periorificial areas on the face, and in sites exposed to trauma (Koebner phenomenon) and, less frequently, in the dorsal area.…”
Section: Introductionmentioning
confidence: 99%
“…(1) It affects 0,5-1 % of the world's population, regardless of race or gender, and it has been observed that more than 50 % of cases occur before the age of 20. (2) This pathology usually presents as acromic and hypochromic macules, with defined borders and a tendency to symmetry. The topography of the lesions is ubiquitous, with a preference for the acral https://doi.org/10.56294/sctconf2023324 and periorificial areas on the face, and in sites exposed to trauma (Koebner phenomenon) and, less frequently, in the dorsal area.…”
Section: Introductionmentioning
confidence: 99%